Dynamic phenotypic shifts and M2 receptor downregulation in bladder smooth muscle cells induced by mirabegron - Muderrisoglu, A. E.; Ciotkowska, A.; Rutz, B.; Hu, S.; Qian, S.; Tamalunas, A.; Stief, C. G.; Hennenberg, M. (Frontiers in Pharmacology, 2024)
Mirabegron is available for treatment of overactive bladder (OAB). However, mechanisms underlying symptom improvements and long-term effects on bladder smooth muscle cells are uncertain. Contractility and growth of bladder smooth muscle contribute to OAB, and depend on smooth muscle phenotypes, and on muscarinic receptor expression. Here, we examined prolonged exposure to mirabegron (20-48 h) on phenotype markers, muscarinic receptor expression, and phenotype-dependent functions in human bladder smooth muscle cells (hBSMC). Methods: Expression of markers for contractile (calponin, MYH11) and proliferative (MYH10, vimentin) phenotypes, proliferation (Ki-67), and of muscarinic receptors were assessed by RT-PCR. Proliferation, viability, actin organization and contractions in cultured hBSMC were examined by EdU, CCK-8, phalloidin staining and matrix contraction assays. Results: Calponin-1 mRNA decreased with 100 nM and 150 nM mirabegron applied for 20 h (0.56-0.6 fold of controls). Decreases were resistant to the β3-AR antagonist L-748,337 (0.34-0.55 fold, 100-150 nM, 20 h). After 40 h, decreases occured in the presence of L-748,337, but not without L-748,337. MYH11 mRNA increased with 150 nM mirabegron (40 h, 1.9 fold). This was partly preserved with L-748,337, but not observed after 20 h mirabegron exposure.Vimentin mRNA reduced with 150 nM mirabegron after 20 h, but not after 40 h, with and without L-748,337 (0.71-0.63 fold). MYH10 mRNA expression remained unaffected by mirabegron. Exposure to 150 nM mirabegron increased Ki-67 mRNA after 20 h in the presence of, but not without L-748,337, and after 40 h without, but not with L-748,337. Proliferation rates and actin organization were stable with 50-150 nM mirabegron (24 h, 48 h). Viability increased significantly after mirabegron exposure for 20 h, and by trend after 40 h, which was fully sensitive to L-748,337. M2 mRNA was reduced by 20 h mirabegron, which was resistant to L-748,337. Carbachol (3 µM) enhanced time-dependent contractions of hBSMC, which was inhibited by mirabegron (150 nM) in late phases (24 hours), but not in early phases of contractions. Conclusion: Mirabegron induces dynamic phenotype alterations and M2 downregulation in hBSMC, which is paralleled by time-shifted anticontractile effects.Phenotype transitions may be involved in improvements of storage symptoms in OAB by mirabegron.